Royal jelly arranges apoptotic and oxidative stress pathways and reduces damage to liver tissues of rats by down-regulation of Bcl-2, GSK3 and NF-?B and up-regulation of caspase and Nrf-2 protein signalling pathways - Aslan, Abdullah; Gok, Ozlem; Beyaz, Seda; Parlak, Gozde; Can, Muhammed Ismail; Gundogdu, Ramazan; Parlak, Akif Evren (Taylor & Francis Ltd, 2023)
Introduction: Royal jelly (RJ) from the honey bee, Apis mellifera, is a traditional product that is widely used as a food supplement to support the medical treatment of various diseases. Material and methods: Our study continued for 8 weeks. 42 Wistar albino (8 weeks old) male rats were used in the study. The study included 6 groups; Group 1: Control group (fed with standard diet), Group 2: RJ (100 mg/kg, bw), Group 3: F-50 (50 mg/kg, bw), group 4: F-100 (100 mg/kg, bw) group 5: F-50 (50 mg/kg, bw) + RJ (100 mg/kg, bw) Group 6: F-100 (100 mg/kg, bw) + RJ (100 mg/kg, bw). Malondialdehyde (MDA), catalase (CAT) and glutathione (GSH) activities in liver tissue were determined by spectrophotometer. Liver tissue samples were examined histopathologically and various protein levels were determined by Western blotting technique. Results: RJ caused a significant decrease in MDA level, Bcl-2, GSK3 and NF-kappa B protein expression levels, whereas induced a significant increase in GSH level, CAT activities and Bax, BDNF, caspase-6, caspase-3, Nrf-2 protein expression levels. Conclusion: Our findings suggest RJ to be used as a hepatoprotective agent in the clinic to modulate the toxic effects of fluoride and other chemicals in the future.
Keywords: Fluoride; liver damage; NF-kappa B; Nrf-2; oxidative stress; royal jelly